Meditasi Kristiani dan Peranannya dalam Pertumbuhan Iman: Suatu Kajian Biblis Dalam Bingkai Mazmur 119:15 - Hadi, Darmawan; Antonius, Yosef; Mesakh, Jacob (Institut Agama Kristen Negeri Tarutung, 2024)
Meditation is a spiritual practice widely known in various religious traditions and beliefs around the world, including Christianity. However, in the context of Christian faith, the understanding and practice of meditation often remain controversial. Some Christians reject meditation because they associate it with non-Christian practices, while others are becoming more open to it, especially through greater access to information. The ambiguity of the concept of meditation in Christianity is an issue that needs to be studied in depth so that believers have a correct and theological understanding. This study aims to explore the meaning of meditation from a biblical perspective, specifically based on Psalm 119:15, and to distinguish it from non-Christian meditation practices. This study uses a qualitative approach with a literature review method and exegetical analysis of biblical texts. The results of the study show that meditation in Christianity centres on reflecting on the Word of God as a means of deepening one's relationship with God and forming a spiritual life rooted in divine truth. Thus, Christian meditation has a strong biblical foundation and differs fundamentally from other religious meditations, particularly in its focus, object of reflection, and spiritual purpose.